Analisis Potensi Energi Angin Sebagai Sumber Alternatif Pembangkit Listrik Di Wonorejo, Situbondo: Analisis Potensi Energi Angin sebagai Sumber Alternatif Pembangkit Listrik di Wonorejo, Situbondo - Mauludina, Nur Ulfa; Arsiani, Mitari Wahyu; Fadhilah, Millatina (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2024)
Renewable energy holds great potential for development in Indonesia, with wind energy being one of the environmentally friendly options. The government has initiated the development of this energy source by publishing a wind map in 2020 to facilitate its utilization. Potential studies indicate that large-scale horizontal wind turbine technology can operate optimally at wind speeds of 5–20 meters per second, while vertical wind turbines are more suitable for small-scale applications at wind speeds below 5 meters per second. This research focuses on the wind energy potential in Wonorejo, Situbondo City, which experiences high wind speeds conducive to the development of wind power plants. With the support of modern technology, this potential can be maximized into electricity generation. The government plans to build a Wind Power Plant (PLTB) in Wonorejo as a concrete step to enhance the contribution of renewable energy. This initiative reflects the government's commitment to supporting national energy independence.